Three-dimensional evaluation of facial morphology in pre-school cleft patients following neonatal cheiloplasty - Dadáková, M; Cagáňová, V; Dupej, J; Hoffmannová, E; Borský, J; Velemínská, J (Journal of cranio-maxillo-facial surgery, 2016)
PURPOSE: To evaluate the facial morphology of pre-school patients with various types of orofacial cleft after neonatal cheiloplasty in pre-school aged children; and to compare facial variability and mean shape with age-corresponding healthy controls. MATERIALS AND METHODS: The sample included 40 patients with unilateral cleft lip (CL), 22 patients with unilateral cleft lip and palate (UCLP), and 10 patients with bilateral cleft lip and palate (BCLP). Patients were divided into two age categories, with a mean age of 3 years and 4.5 years, respectively. The group of healthy age-matched controls contained 60 individuals. Three-dimensional virtual facial models were evaluated using geometric morphometry and multivariate statistics methods. RESULTS: Statistically significant differences were found between each of the cleft groups and the controls. Color-coded maps showed facial shape deviations, which were located mainly in the nasal area and philtrum in all groups examined, and also in the buccal region and the chin in patients with UCLP or BCLP. These differences became more apparent, but not significantly so, in the older age category. CONCLUSION: Facial deviations typical of patients with clefts were observed in all of the patient groups examined. Although the analysis showed statistically significant differences in overall facial shape between patients and controls among all groups tested, the facial morphology in patients who have undergone only neonatal cheiloplasty (CL) is influenced to a small extent and may be considered satisfactory. More severe cleft types (UCLP, BCLP) together with palatoplasty, are reflected in more marked impairments in facial shape.
Keywords: Imaging, Three-Dimensional; Anatomic Landmarks; anatomická značka; Cleft Lip; Humans; Case-Control Studies; studie případů a kontrol; Female; lidé; Cleft; Face shape; předškolní dítě; Geometric morphometry; ženské pohlaví; Male; maxilofaciální vývoj; Cleft Palate; Maxillofacial Development; zobrazování trojrozměrné; rozštěp patra; rozštěp rtu; mužské pohlaví; Neonatal cheiloplasty; Child, Preschool; 3D imaging